Impact of COVID-19 Pandemic on Laboratory Utilization. (14th July 2020) - Durant, Thomas J S; Peaper, David R; Ferguson, David; Schulz, Wade L
Abstract: Background: Coronavirus disease 2019 (COVID-19) was formally characterized as a pandemic on March 11, 2020. Since that time, the COVID-19 pandemic has led to unprecedented demand for healthcare resources. The purpose of this study was to identify changes in laboratory test utilization in the setting of increasing local incidence of COVID-19. Methods: We performed a retrospective assessment of laboratory test order and specimen container utilization at a single, urban tertiary care medical center. Data were extracted from the laboratory information system database over a 10-week period, spanning the primordial inflection of COVID-19 incidence in our region. Total testing volumes were calculated during the first 2 and last 2 weeks of the observation period and used as reference points to examine the absolute and relative differences in test order volume between the prepandemic and COVID-19 surge periods. Results: Between February 2, 2020, and April 11, 2020, there were 873 397 tests ordered and final verified. The in-house SARS-CoV-2 PCR positivity rate for admitted patients in the last week of the observation period was 30.8%. Significant increases in workload were observed in the send-out laboratory section and for COVID-19 diagnosis (PCR) and management-related testing. Otherwise, there was a net decrease in overall demand across nearly all laboratory sections. Increases in testing were noted for tests related to COVID-19 management. Viral transport media and citrated blue top containers demonstrated increases in utilization. Conclusion: Increasing local incidence of COVID-19 had a profound impact on laboratory operations. While volume increases were seen for laboratory tests related to COVID-19 diagnostics and management, including some with limited evidence to support their use, overall testing volumes decreased substantially. During events such as COVID-19, monitoring of such patterns can help inform laboratory management, staffing, and test stewardship recommendations for managing resource and supply availability.